Epidemiology and neonatal pain management of heelsticks in intensive care units: EPIPPAIN 2, a prospective observational study. (July 2016) - Courtois, Emilie; Droutman, Stéphanie; Magny, Jean-François; Merchaoui, Zied; Durrmeyer, Xavier; Roussel, Camille; Biran, Valérie; Eleni, Sergio; Vottier, Gaëlle; Renolleau, Sylvain; Desfrere, Luc; Castela, Florence; et al.
Abstract: Background: Heelstick is the most frequently performed skin-breaking procedure in the neonatal intensive care units (NICUs). There are no large multicenter studies describing the frequency and analgesic approaches used for heelsticks performed in NICUs. Objectives: To describe the frequency of heelsticks and their analgesic management in newborns in the NICU. To determine the factors associated with the lack of specific preprocedural analgesia for this procedure. Design: EPIPPAIN 2 (Epidemiology of Procedural PAin In Neonates) is a descriptive prospective epidemiologic study. Setting: All 16 NICUs in the Paris region in France. Participants: All newborns in the NICU with a maximum corrected age of 44 weeks +6 days of gestation on admission who had at least one heelstick during the study period were eligible for the study. The study included 562 newborns. Methods: Data on all heelsticks and their corresponding analgesic therapies were prospectively collected. The inclusion period lasted six weeks, from June 2, 2011 to July 12, 2011. Newborns were followed from their admission to the 14th day of their NICU stay or discharge, whichever occurred first. Results: The mean (SD) gestational age was 33.3 (4.4) weeks and duration of participation was 7.5 (4.4) days. The mean (SD; range) of heelsticks per neonate was 16.0 (14.4; 1–86) during the study period. Of the 8995 heelsticks studied, 2379 (26.4%) were performed with continuous analgesia, 5236 (58.2%) with specific preprocedural analgesia. Overall, 6764 (75.2%) heelsticks were performed with analgesia (continuous and/or specific). In a multivariate model, the increased lack of preprocedural analgesia was associated with female sex, term birth, high illness severity, tracheal or noninvasive ventilation, parental absence and use of continuous sedation/analgesia. Conclusions: Heelstick was very frequently performed in NICUs. Although, most heelsticks were performed with analgesia, this was not systematic. The high frequency of this procedure and the known adverse effects of repetitive pain in neonates should encourage the search of safe and effective strategies to reduce their number.